CONCEPT OF DRUG LIKENESS IN PHARMACEUTICAL RESEARCH - PRERANA B. JADHAV,; AKSHAY R.YADAV,; MEGHA G. GORE, (International Journal of Pharma and Bio Sciences, 2015)
The low success rate of converting lead compounds into drugs owing to unfavorable pharmacokinetic parameters has evoked a renewed interest in understanding more clearly what makes a compound drug-like. The concept of drug-likeness, established from the analyses of the physiochemical properties or/and structural features of existing small organic drugs or/and drug candidates, has been widely used to ï¬lter out compounds with undesirable properties. Present review summarise molecular property filters and the number of computational techniques for identifying drug-like molecules.